Development of solar powered mobile robot - Syed Musa Kazim, Syed Zainal Abidin (2013)
Wheel mobile robots (WMRs) have been famous since over the past three decades in research and development of mobile robot. This is due to its advantages over legged mobile robot which are wheel mobile robot having no stability problem and quicker in smooth surface compared to legged-robot. Furthermore, wheel mobile robot is more energy efficient than legged-robot and also simpler in design parts thus it is widely applied in the industry. The development of mobile robot has benefit human in many ways. The advantage of robot that benefit human very much is that robot does not feel tired even after days of doing the same task it can do work for a very long time without rest, robot also can do repetitive task with appropriate speed and with high accuracy and precision. Mobile robot is a robot that can move freely in its environments to do its tasks. However, the limitation of mobile robot is mobile robot depending on the capacity of power source from the batteries. When the batteries have drained out of power, the robot cannot continue its current operation until the batteries is recharged